Acute response of sclerostin to whole-body vibration with blood flow restriction - Gapper, K. S; Stevens, S.; Antoni, R.; Hunt, J.; Allison, S. J. (International Journal of Sports Medicine, 2021)
Blood flow restriction may augment the skeletal response to whole-body vibration. This study used a randomised, crossover design to investigate the acute response of serum sclerostin and bone turnover biomarkers to whole-body vibration with blood flow restriction. Ten healthy males (mean±standard deviation; age: 27±8 years) completed two experimental conditions separated by 7 days: (i) whole-body vibration (10 1-minute bouts of whole-body vibration with 30 s recovery) or (ii) whole-body vibration with lower-body blood flow restriction (10 cycles of 110 mmHg inflation with 30 s deflation during recovery). Fasting blood samples were obtained immediately before and immediately after exercise, then 1 hour, and 24 hours after exercise. Serum samples were analysed for sclerostin, cross-linked C-terminal telopeptide of type I collagen, and bone-specific alkaline phosphatase. There was a significant time × condition interaction for bone-specific alkaline phosphatase (p=0.003); bone-specific alkaline phosphatase values at 24 hours post-exercise were significantly higher following whole-body vibration compared to combined whole-body vibration and blood flow restriction (p=0.028). No significant time × condition interaction occurred for any other outcome measure (p>0.05). These findings suggest that a single session of whole-body vibration combined with blood flow restriction does not significantly affect serum sclerostin or bone turnover biomarkers.